The conference on the mobilization of savings in Africa - International Savings Bank Institute; Cassa Di Risparmio Delle Provincie Lombarde (Lobardi : International Savings Bank Institute, 1971)
The conference emphasizes the fact that African governments are acutely conscious of the urgent need to mobilize an increased volume of domestic financing in order to achieve a sustained economic growth and promote the well-being of their population.
Proceedings of a conference organized under the patronage of the President of the Republic of Italy by the International Savings Banks Institute and the Cassa di Risparmio Delle Provincie Lombarde in Milan, 20-23 September, 1971.
occ 17/01/2019
Loans
Keywords: Agricultural credit; Banks and banking; Africa